Tinjauan Yuridis Penyelesaian Sengketa Terhadap Alas Hak Atas Tanah (Studi Putusan Nomor: 347/PDT/2014/PT-Mdn) - Krisman Antonius Zandroto; Marsella Marsella; Alvin Hamzah Nasution (Universitas Medan Area, 2021)
Land disputes are unavoidable today, this is because various land needs are very high in today's times while the number of land parcels is limited. This demands improvements in the field of land management and use for the welfare of the community and especially legal certainty. The research method used in this paper is a normative juridical method. The research method used is library research and field research. Arrangement of rights regarding the basis of land rights as regulated in Law No. 5 of 1996 concerning Basic Agrarian Principles, regulating several land rights that are on the earth's surface, under the earth's surface, and above the air. The factors causing the frequent emergence of land dispute problems include: the land administration system, especially in terms of land certification, which is not right, the distribution of land ownership is not evenly distributed, the legality of land ownership is based solely on formal evidence (certificates), without regard to productivity. soil. The process of resolving disputes over land rights in decision number: 347 / Pdt / 2014 / PT-Mdn is resolved through the litigation channel, where in the litigation line the judiciary is given the authority to hold authority and adjudicate a dispute. In every dispute resolution process through litigation, the parties involved in the dispute must follow the procedures set out in the procedural law.